“I saw it on Instagram”. Media consumption and media literacy on High-schoolers from working- and middle-class background in Chile - Lazcano-Peña, Daniela (2023)
This article characterizes the media competencies and information consumption of 79 students aged between 15 and 17 from subsidized and municipal educational establishments in Antofagasta, Valparaíso, and Metropolitan (Chile). Through group interviews, the participants demonstrate a critical view of traditional media (print, radio, television) and express more confidence in the algorithmic functioning of social media, especially Instagram, as an information source. The results pose challenges for media literacy among young people in educational and extracurricular contexts.